DESIGN OF M-LEARNING BASED ON HOME SCIENCE PROCESS SKILL FOR SCIENCE LEARNING - Mariatul Qibtiah; Yayat Ruhiat; Sholih Sholih (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
Instructional media that are innovative and easy are really needed by students in the current situation. M-learning based on Home Science Process Skill (HSPS), is an innovative learning medium that applies science learning directly in life, with the guidance of parents at home and teachers. The study aims to produce design of m-learning based on home science process skill for science learning. This research was conducted in April 2021 at SMPN 30 Kota Tangerang. The method used was the Research and Development (R&D) research method with the Instructional Development Institute (IDI) model. The stages of research and development of learning media were to define stage, develop stage and evaluate stage. The results of the feasibility test for the design of m-learning based on Home Science Process Skill by media experts and material experts obtained an average assessment of 78.40% and 87.50% with good and very good interpretations. The conclusion of this research was that the design of this learning media was feasible to be used as a medium for student learning media.